2019
DOI: 10.1186/s13287-019-1261-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of primordial germ cells from premature ovarian insufficiency-derived induced pluripotent stem cells

Abstract: Background Premature ovarian insufficiency (POI) is a common disease in reproductive women. The pathogenesis of POI is not clear, although it is known that it involves the disorder of oocyte differentiation and development. The introduction of reprogramming human somatic cells into induced pluripotent stem cells (iPSCs) offers a unique opportunity to study many aspects of POI from cell differentiation in vitro that could ultimately lead to novel drug development and testing to help treat the disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…After the researchers demonstrated mouse oocytes from granulosa cell-derived iPSCs possess a higher germline competency than other cell lines, the certain human granulosa cells discarded after IVF were also considered as a more permissive cell source for iPSCs to generate oocytes [ 58 ]. Human iPSCs could provide patient-specific PSCs which could be used to investigate disease-specific pathogenesis in vitro [ 26 , 82 , 83 ]. Recently, a study established human iPSCs in 4i medium from patients with premature ovarian insufficiency.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the researchers demonstrated mouse oocytes from granulosa cell-derived iPSCs possess a higher germline competency than other cell lines, the certain human granulosa cells discarded after IVF were also considered as a more permissive cell source for iPSCs to generate oocytes [ 58 ]. Human iPSCs could provide patient-specific PSCs which could be used to investigate disease-specific pathogenesis in vitro [ 26 , 82 , 83 ]. Recently, a study established human iPSCs in 4i medium from patients with premature ovarian insufficiency.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Compared to the previous human PGCLCs induction methods, the addition of DNA methyltransferase inhibitor enhanced human PGCLCs induction. Thus, they provided a complementary way for human PGC differentiation from patient-specific iPSCs [ 82 ]. Furthermore, the PSCs pluripotent state was also considered as an important factor during induction.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Organoids can be derived from induced pluripotent stem cells (iPS cells) and can be used to model normal and abnormal development. For the gonad, iPS cells have been used to generate Sertoli-like cells, and also Leydig and germ cells [ 182 , 183 , 184 , 185 ]. Single-cell RNA-seq could be used to chart the differentiation of these cell types, identifying important genes activated during formation of the testis.…”
Section: Single-cell -Omics In Gonadal Diseasementioning
confidence: 99%
“…In human female iPSCs, Eguizabal et al showed that overexpression of DAZL and BOULE can also lead iPSCs to enter meiosis. Yang et al [105] used fibroblasts from premature ovarian insufficiency (POI) patients to successfully differentiate them into PGCs that had the potential for meiotic progression in vitro. Mimicking the natural role of the oocyte by stimulation with GDF9 and BMP15 proved further induction of folliculogenesis in differentiated PGCs [108].…”
Section: Modeling the Complexity: Human Ipscs-derived Models For Dmentioning
confidence: 99%